Investigating Challenges in Arabic Vocabulary Mastery Among Students at MTs Nahdlatul Ulama Maesan Bondowoso - Khotimah, Husnul; Nurlaila, Nisfi (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2024)
This research is inspired by the importance of Arabic vocabulary mastery as the foundation of Arabic language proficiency. Initial observations in class 8 of MTs Nahdlatul Ulama Maesan Bondowososhowed that most students still have difficulties in mastering and using Arabic vocabulary in daily learning. This impacts their low ability in Arabic language skills such as reading, writing, and speaking. This study aims to analyze the level of Arabic vocabulary mastery among students of class 8 MTs Nahdlatul Ulama Maesan Bondowosoand identify factors that influence their vocabulary mastery. The research method used is descriptive qualitative with data collection techniques through vocabulary mastery tests, learning observations, interviews with teachers and students, and documentation. The results showed that the level of Arabic vocabulary mastery among students in class 8 is still relatively low, with an average score of 65.5 out of a maximum score of 100. The influencing factors include lack of learning motivation, insufficient practice in using vocabulary during learning, and limited learning media supporting Arabic vocabulary mastery.